STUDY OF THE CHEMICAL AND MINERALOGICAL COMPOSITION OF THERMAL POWER PLANT WASTES - Mallabayev, Odiljon; Nazhimova, Nursuluu; Seitnazarova, Oksana; Abdukodirov, Elyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The paper presents the results of a comparative study of ash–sludge wastes generated from the combustion of coal and natural gas at the Takhiatash Thermal Power Plant. Using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) methods, the morphological and chemical differences between the studied samples were determined. It was shown that coal-derived ash–sludge wastes are characterized by a porous, heterogeneous structure and a high content of silicon, aluminum, and calcium; whereas gas-derived wastes predominantly contain iron oxides and exhibit a denser and more homogeneous structure. The obtained results indicate the potential applicability of these technogenic materials as sorbents, catalysts, and additives in construction composites.